Keragaman Pola Membangun Kapabilitas Inovasi Organisasional - Sulistyohadi, Timbul (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
Based on literature review, questionnaire result, and in-depth interview to 78 head of bag producers, this study success to identify four patterns of innovation capability building; 2 patterns based on producer size, and 2 patterns based on producer operational time. In general, this study concludes only two patterns of innovation capability building which based on producer operational time.